High-throughput drug screening identifies fluoxetine as a potential therapeutic agent for neuroendocrine prostate cancer - Chen, Lei; Ji, Yiyi; Li, Ang; Liu, Bo; Shen, Kai; Su, Ruopeng; Ma, Zehua; Zhang, Weiwei; Wang, Qi; Zhu, Yinjie; Xue, Wei (Frontiers in Oncology, 2023)
Introduction Neuroendocrine prostate cancer (NEPC) is an aggressive subtype of prostate cancer with poor prognosis and resistance to hormone therapy, which has limited therapeutic approaches. Therefore, this study aimed to identify a novel treatment for NEPC and provide evidence of its inhibitory effects. Methods We performed a high-throughput drug screening and identified fluoxetine, originally an FDA-approved antidepressant, as candidate therapeutic agent for NEPC. We carried out both in vitro and in vivo experiments to demonstrate the inhibitory effects of fluoxetine on NEPC models and its mechanism in detail. Results Our results demonstrated that fluoxetine effectively curbed the neuroendocrine differentiation and inhibited cell viability by targeting the AKT pathway. Preclinical test in NEPC mice model (PBCre4: Ptenf/f; Trp53f/f; Rb1f/f) showed that fluoxetine effectively prolonged the overall survival and reduced the risk of tumor distant metastases. Discussion This work repurposed fluoxetine for antitumor application, and supported its clinical development for NEPC therapy, which may provide a promising therapeutic strategy.